Pemodelan airtanah dan Neraca Airtanah Dampak Penambangan Batubara Open Pit pada Lipatan Sinklin di Daerah Muara Lawa, Kabupaten Kutai Barat, Provinsi Kalimantan Timur - Devy, Shalaho Dina (SPECTA Journal of Technology, 2018)
Ch a n g e s in land use impacts on groundwater availability both in quality and quantity. Study of geological, hydrogeological conditions, hydrological, hydrogeological boundary conditions contribute to determine the presence of groundwater in the groundwater basin and determine the natural groundwater flow modeling patterns. Location of the study are in Muara Lawa, including the formation Pulaubalang, Pamaluan, and Balikpapan on Lampanan syncline structure. Exploration drilling results indicate, that the hydrogeological study area into the aquifer system of folded sedimentary rocks consisting of seven aquifer layers alternating between akuitar, aquifers, and the base layer in the form of akuiklud. The area bounded by the limits of the model study of surface water in two major rivers, the Lawa River (east) and the Perak River (west), as well as the groundwater divide with the highest head (north and south. The results of the analysis of the type of regional aquifers aquifer models including the category of semi depressed with aquitards dominance in the surface layer. The pattern of groundwater flow and head height can be predicted by modeling using Visual Modflow. There is an increase zone budget is almost five times higher than the natural condition to the active mining conditions, particularly in the green zone, that of the natural conditions of 1,502 m3 day-1 to 12,930 m3 day-1 in the active mining. This is due, in the mining area there is a change in land use and hidrostratigrafi, namely the formation of pits that reach depths of 70 meters.